The Ethics of Sense-Making - Candiotto, Laura; Weichold, Martin (My University, 2023)
In this paper, we contribute to the arising field of “enactive ethics,” that is, the application of enactive cognitive science to the field of ethics. To this end, we will make a case that an “ethics of sense-making” should exist. With “sense-making,” we mean the permanent everyday embodied activity of interpreting the surroundings we are in, as well as our role in them. In other words, we mean the activity of understanding our environments in such a way that certain things, but not others, stand out as meaningful and relevant to us. We argue that sense-making can be performed in ethically better or worse ways. For example, one might make sense of a potentially provocative comment either as an insult or as an invitation for a respectful discussion. How one makes sense in this case will affect oneself, the other, and their present and future relations. We propose that it is often helpful to hold humans responsible for their ways of sense-making. This opens up the possibility to transform their sense-making and the worlds they inhabit. This also has significance for their eudaimonic well-being. Our ethics of sense-making focusses on the ubiquitous activities of sense-making, which, when changed, will lead to great ethical improvements of people’s actions, choices, and character traits.
Etika tvorby smyslu
Keywords: enactive ethics; sense-making; participatory sense-making; interpretation; world-making; self-making; eudaimonic well-being; mindfulness-based ethics; enaktivní etika; vytváření smyslu; participativní vytváření smyslu; interpretace; vytváření světa; vytváření sebe sama; eudaimonická pohoda; etika založená na všímavosti.